Surat Keputusan Pengangkatan Pegawai Sebagai Jaminan Kredit Di Bank - Tika Andarasni Parwitasari (Jurnal Ilmiah SINUS, 2011)
Economic conditions and development in Indonesia can not be separated from the role of the banking sector, role or function of banking here is as a "financial intermediary" with the main activities to collect and distribute public funds.One of the main activities of the bank was channeling funds to community activities or the provision of credit. Bank in channeling funds or provide credit must be adhered to the principle of prudence as well as holding a binding guarantee or collateral. The aim of prudential banking principles is to prevent the banks mistake in order to be right targeted in selecting and determining who is eligible to become his customers or debtors. The purposes of Binding guarantee or collateral are when the debtor is no longer has the ability to pay its debts, the banks can use collateral to pay off debts. Usually the collateral is in the form of assets or goods that have high economic value.Someone at the time accepted and appointed as an officials or staff, then to him will be given a hiring decision letter. This letter was present as a financial solution for those who need credit but do not have high economic value of assets, now that banks can provide loans secured by the hiring decision letter.Keywords : Bank, credit guarantee